Systemically circulating 17β-estradiol enhances the neuroprotective effect of the smoking cessation drug cytisine in female parkinsonian mice - Sara M. Zarate; Roger C. Garcia; Gauri Pandey; Rahul Srinivasan (npj Parkinson's Disease)
Abstract The smoking cessation drug cytisine exerts neuroprotection in substantia nigra pars compacta (SNc) dopaminergic (DA) neurons of female but not male 6-hydroxydopamine (6-OHDA) lesioned parkinsonian mice. To address the important question of whether circulating 17β−estradiol mediates this effect, we employ two mouse models aimed at depleting systemically circulating 17β-estradiol: (i) bilateral ovariectomy (OVX), and (ii) aromatase inhibition with systemically administered letrozole. In both models, depleting systemically circulating 17β-estradiol in female 6-OHDA lesioned parkinsonian mice results in the loss of cytisine-mediated neuroprotection as measured using apomorphine-induced contralateral rotations and SNc DA neurodegeneration. Our experiments also reveal that OVX alone exerts neuroprotection in SNc DA neurons due to compensatory changes not observed in the letrozole model, which underscores the importance of using independent models of 17β-estradiol depletion to study neuroprotection. Taken together, our findings suggest that the smoking cessation drug cytisine is a viable neuroprotective drug for pre-menopausal women with Parkinson’s disease.